2020
DOI: 10.1128/msystems.00903-19
|View full text |Cite
|
Sign up to set email alerts
|

manta: a Clustering Algorithm for Weighted Ecological Networks

Abstract: Microbial network inference and analysis have become successful approaches to extract biological hypotheses from microbial sequencing data. Network clustering is a crucial step in this analysis. Here, we present a novel heuristic network clustering algorithm, manta, which clusters nodes in weighted networks. In contrast to existing algorithms, manta exploits negative edges while differentiating between weak and strong cluster assignments. For this reason, manta can tackle gradients and is able to avoid cluster… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Microbial network inference algorithms usually return "hairballs" of densely interconnected taxa that require further analysis to yield testable hypotheses. But despite the wealth of inference tools, only a few analysis tools dedicated to microbial networks have been developed to date [37][38][39]. Two types of network analysis are particularly informative: data integration and clustering.…”
Section: Challenge #7: How To Benchmark Microbial Network Construction On Biological Data?mentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial network inference algorithms usually return "hairballs" of densely interconnected taxa that require further analysis to yield testable hypotheses. But despite the wealth of inference tools, only a few analysis tools dedicated to microbial networks have been developed to date [37][38][39]. Two types of network analysis are particularly informative: data integration and clustering.…”
Section: Challenge #7: How To Benchmark Microbial Network Construction On Biological Data?mentioning
confidence: 99%
“…Such taxon groups often covary in response to environmental factors such as pH and temperature, and therefore de novo clustering is a means to uncover niche structure. For instance, the members of different clusters in a cheese microbial network respond differently to moisture [37]. In the second case, taxa are assigned to clusters according to prior knowledge, for instance, their plankton function type [9] or their phylum.…”
Section: Challenge #7: How To Benchmark Microbial Network Construction On Biological Data?mentioning
confidence: 99%
“…Therefore, taxa in the CAN were compared to taxa reported as indicators of high microbial abundance (HMA) or low microbial abundance (LMA) [32]. CAN network clusters were identified with manta v1.0.0 [33], as this algorithm has been designed to handle negative edges in the CAN. To run the clustering algorithm, default settings were used, except the number of iterations and permutations, which was set to 200.…”
Section: Case Studiesmentioning
confidence: 99%
“…Only correlations between environmental variables and species that were signi cant (P < 0.05, Benjamini-Hochberg adjust) and strong (r ≥ 0.75 or r ≤ -0.75) were considered. A novel microbial association network clustering algorithm (Manta) (version 1.0.1), which determines the optimal cluster number automatically, was used to separate the networks into clusters with default settings [22] after calculating the global network based on all 54 samples across the regime shift from MDR to PDR. Indexes, including modularity, clustering coe cient, average path length, network diameter, average degree and graph density were calculated using the 'igraph' packages in R to describe the attributes of a network [45].…”
Section: Network Analysismentioning
confidence: 99%
“…This procedure demonstrated that both stochastic and deterministic processes appear to govern the assembly processes of bacterial communities [20,21]. However, a more complete understanding of community composition in the context of eutrophic lakes requires a thorough description of the abiotic drivers of co-occurrence patterns [22]. An inter-regime bacterioplankton co-occurrence network can demonstrate how clusters of organisms are driven by abiotic factors along regime shifts in freshwater lakes [23,24].…”
Section: Introductionmentioning
confidence: 98%